2020
DOI: 10.1002/adma.202003712
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Unique Alignment of Cobalt Ferrite Nanoparticles, Mild Hyperthermia, and Controlled Intrinsic Cobalt Toxicity for Cancer Therapy

Abstract: Nanoparticle‐based magnetic hyperthermia is a well‐known thermal therapy platform studied to treat solid tumors, but its use for monotherapy is limited due to incomplete tumor eradication at hyperthermia temperature (45 °C). It is often combined with chemotherapy for obtaining a more effective therapeutic outcome. Cubic‐shaped cobalt ferrite nanoparticles (Co–Fe NCs) serve as magnetic hyperthermia agents and as a cytotoxic agent due to the known cobalt ion toxicity, allowing the achievement of both heat and cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
87
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 49 publications
0
87
2
1
Order By: Relevance
“…Finally, the resulting Co particles were oxidized in pure oxygen gas at 900 • C for different time durations, namely 15, 60, 300, and 540 min, resulting in the samples that are denoted as l (15), l(60), l(300), and l(540), respectively. (ii) For the s-series, the Co(OH) 2 precursor was not calcined in air but directly reduced in hydrogen at (only) 300 • C, which allowed the formation of metallic Co particles, and subsequently oxidized also at the relatively low temperature of 300 • C for different treatment durations, resulting in the samples we label as s (10), s (20), s (40), and s(80), where the numbers give the duration of the oxidation treatment in minutes.…”
Section: Synthesis Of Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the resulting Co particles were oxidized in pure oxygen gas at 900 • C for different time durations, namely 15, 60, 300, and 540 min, resulting in the samples that are denoted as l (15), l(60), l(300), and l(540), respectively. (ii) For the s-series, the Co(OH) 2 precursor was not calcined in air but directly reduced in hydrogen at (only) 300 • C, which allowed the formation of metallic Co particles, and subsequently oxidized also at the relatively low temperature of 300 • C for different treatment durations, resulting in the samples we label as s (10), s (20), s (40), and s(80), where the numbers give the duration of the oxidation treatment in minutes.…”
Section: Synthesis Of Samplesmentioning
confidence: 99%
“…Most exchange bias (EB) applications are based on thin films, such as spin valve structures [15][16][17]; however, EB effects are prevalent in NP-based materials used, for example, in permanent magnets and certain biomedical technology [1,2,7,18,19] (magnetic hyperthemia is one such biomedical application, where, recently, the associated toxicity of Co-containing NPs was suggested as a way to improve cancer therapeutic outcome [20]). Moreover, exchange coupling is an effective way to magnetically stabilize small FM particles against thermal fluctuations and, thus, it has been proposed as a strategy to design high-density magnetic recording media [1,2,17,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…[12,13] The deep penetration of magnetic fields within the human body, together with the possibility of targeting MNPs to specific tissues, have enabled minimally invasive, local, and remotely activated heating showing high efficacy at the in vitro and in vivo levels. [14][15][16][17][18][19][20][21][22][23] Clinical trials have shown the efficacy of MHT to treat solid tumors, as well as to increase the usefulness of chemotherapy by enhancing drug permeability of cancer tissues. [24,25] Reaching high standards of efficacy and selectivity in MHT treatments requires full control over the remote heating process, which means precise localization of the MNPs and real-time thermal feedback into the treated tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, magnetite is extremely sensitive to oxidation, decreasing its magnetic properties; thus, it requires a protective capping layer [16,17]. Cobalt and nickel ferrites are often considered as alternatives to magnetite [18,19]. These materials are attractive due to their high chemical stability and significant magnetism.…”
Section: Introductionmentioning
confidence: 99%